The effects of ceftriaxone on cue-primed reinstatement of cocaine-seeking in male and female rats: estrous cycle effects on behavior and protein expression in the nucleus accumbens - Bechard, Allison R. (Psychopharmacology (Berl), 2017)
RATIONALE: Effective pharmacological treatments to prevent cocaine relapse remain elusive. In male rats, ceftriaxone attenuates the reinstatement of cocaine-seeking while increasing glutamate transporter-1 (GLT-1) and xCT expression in the nucleus accumbens core (NAc). Despite reported sex differences in cocaine relapse, these effects have not yet been confirmed in female rats. OBJECTIVE: We investigated the effects of ceftriaxone on cue-primed reinstatement and cocaine-induced alterations in glutamatergic proteins in the NAc of female rats. Potential interactions between estrous phase and treatment were also assessed. METHOD: Male and female rats self-administered cocaine in the presence of discrete cues for 12 days, followed by 2–3 weeks of extinction. Ceftriaxone or vehicle was administered daily for a minimum of 6 days immediately preceding a cue-primed reinstatement test. RESULTS: Total cocaine intake was greater in females than in males, but reinstatement behavior was similar. Ceftriaxone attenuated reinstatement in both sexes and was accompanied by increased expression of GLT-1a and xCT in the NAc. However, ceftriaxone attenuated reinstatement only when females were tested during met-, di-, and proestrus phases and not during estrus. A significant increase in AMPA receptor subunit GluA1 surface expression was also observed during estrus, potentially influencing reinstatement. CONCLUSION: These findings extend the beneficial effects of ceftriaxone on persistent cocaine-seeking from males to females, increasing its potential as a pharmacological treatment for preventing relapse. The effects of estrus on GluA1 expression and reinstatement observed here indicate that females may need additional interventions during some phases of the menstrual cycle.